1995
DOI: 10.1029/95jd01835
|View full text |Cite
|
Sign up to set email alerts
|

Organics alter hygroscopic behavior of atmospheric particles

Abstract: The optical and chemical properties of atmospheric particles and their ability to act as cloud condensation nuclei (CCN) depend strongly upon their affinity for water. Laboratory experiments have shown that water soluble substances such as ammonium sulfate, ammonium nitrate, and sodium chloride, which are major inorganic components of atmospheric particles, absorb water in an amount proportional to water vapor pressure. Analogous information about the interactions between water and organics, which are another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
477
2
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(489 citation statements)
references
References 68 publications
7
477
2
3
Order By: Relevance
“…In this context, sulfate and POM are treated independently such that f ssp (RH) for sulfate is based on theoretical calculations or laboratory measurements while POM is assumed to be hydrophobic or to have f ssp (RH) scalable to or equal to that of sulfate [e.g., Haywood et al, 1999;Chin et al, 2002]. However, both laboratory and field measurements indicate that POM that is internally mixed with water soluble salts can reduce the particles' hygroscopic response, which decreases their water content and their ability to scatter light at elevated relative humidities [e.g., Saxena et al, 1995;Carrico et al, 2005]. The complexity of the composition of POM and its impact on aerosol optical properties requires the development of simplifying parameterizations that allow for the incorporation of information derived from field measurements into calculations of DCF and visibility [Kanakidou et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, sulfate and POM are treated independently such that f ssp (RH) for sulfate is based on theoretical calculations or laboratory measurements while POM is assumed to be hydrophobic or to have f ssp (RH) scalable to or equal to that of sulfate [e.g., Haywood et al, 1999;Chin et al, 2002]. However, both laboratory and field measurements indicate that POM that is internally mixed with water soluble salts can reduce the particles' hygroscopic response, which decreases their water content and their ability to scatter light at elevated relative humidities [e.g., Saxena et al, 1995;Carrico et al, 2005]. The complexity of the composition of POM and its impact on aerosol optical properties requires the development of simplifying parameterizations that allow for the incorporation of information derived from field measurements into calculations of DCF and visibility [Kanakidou et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…The hygroscopic properties of inorganic particles are altered substantially when organics are present [Andrews and Larson, 1993;Saxena et al, 1995]. Organics may either enhance or diminish water uptake, depending upon whether the organic matter is primary, urban and hydrophobic or secondary, nonurban and more hydrophilic [Saxena et al, 1995] [Hanson, 1995;de Gouw and Lovejoy, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…Primary carbonaceous particles originate largely from petroleum combustion and biological matter. Secondary particles are formed from condensation of low vapor pressure products following photooxidation of organic gases during their residence in the atmosphere [Saxena et al, 1995]. Condensation of organic species on existing inorganic aerosol will form an outer organic film encompassing an inner aqueous or solid core [Gill and Graedel, 1983].…”
Section: Introductionmentioning
confidence: 99%
“…For example, addition of SOA to the increasingly acidic hygroscopic particles may be enhanced through acid-catalyzed reactions [Jang et al, 2002;Czoschke et al, 2003]. Many recent studies [Hansson et al, 1990;Saxena et al, 1995;Hansson et al, 1998;Xiong et al, 1998] have shown that organics may significantly change the DRH and CRH of a hygroscopic aerosol and may also cause it to absorb water prior to deliquescence.…”
Section: Discussionmentioning
confidence: 99%